Modulation of negative emotions through anodal tDCS over the right ventrolateral prefrontal cortex. (October 2018) - Vergallito, Alessandra; Riva, Paolo; Pisoni, Alberto; Romero Lauro, Leonor J.
Abstract: Increasing evidence suggests that the right ventrolateral prefrontal cortex (rVLPFC) plays a critical role in emotion regulation, in particular concerning negative feelings. In the present research, we applied anodal transcranial direct current stimulation (tDCS) over the rVLPFC with a twofold purpose. First, we aimed at exploring the feasibility of modulating the subjective experience of emotions through tDCS in healthy participants. Second, we wanted to assess which specific emotion can be regulated (and which cannot) with this brain stimulation approach. We designed a double-blind, between-subjects, sham-controlled study in which 96 participants watched short video clips eliciting different emotions during anodal or sham tDCS over the rVLPFC. Emotional reactions to each video clip were assessed with self-report scales measuring eight basic emotions. Results showed that, in contrast to the sham condition, tDCS over the rVLPFC reduced the perceived extent of specific negative emotions, namely, fear, anxiety, and sadness, compared to other negative or positive feelings. Overall, these results support the role of rVLPFC in regulating negative emotions, mostly associated with the prevention of dangerous situations (i.e., fear, anxiety, and sadness). Highlights: Anodal tDCS over rVLPFC modulated negative emotion perception. TDCS specifically reduced anxiety and fear induced by video clips. rVLPFC is involved in the regulation of certain negative emotions. Anodal tDCS can be effectively used to boost emotion regulation.